2016
DOI: 10.31989/ffhd.v6i9.285
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Grape Wine and Apple Cider Vinegar on Oxidative and Antioxidative Status in High Cholesterol-Fed Rats

Abstract: Background:Oxidative stress is the result of an imbalance between the rates of free radical production and elimination via endogenous antioxidant mechanisms such as antioxidant enzymes, which include glutathione peroxidase (GSH-Px), superoxide dismutase (SOD), and catalase (CAT). There are mainly two vinegar production methods. The first is the surface method which is also known as the traditional method. The second method is known as the industrial method or submerged method which involves the use of a submer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Apple vinegar has been used since ancient times in folk medicine to prevent and treat different ailments such as diabetes, hyperlipidemia and oxidative stress [33,[53][54][55][56][57][58]. The results of the quantification of phenolic and flavonoid contents revealed that apple vinegar contains high concentrations of these molecules, which is in line with previous studies [36,59].…”
Section: Discussionsupporting
confidence: 83%
“…Apple vinegar has been used since ancient times in folk medicine to prevent and treat different ailments such as diabetes, hyperlipidemia and oxidative stress [33,[53][54][55][56][57][58]. The results of the quantification of phenolic and flavonoid contents revealed that apple vinegar contains high concentrations of these molecules, which is in line with previous studies [36,59].…”
Section: Discussionsupporting
confidence: 83%
“…In 2000 Lu and Foo 71 carried out a study that showed the antioxidant and free radical scavenging activity of apple cider vinegar containing polyphenolic compounds. In 2016 Seydim et al 72 made an experimental model on rats for evaluation of the antioxidant potential of apple cider vinegar and grape vinegar. In 2018 Yagnik et al 73 observed the antimicrobial activity of ACV against various bacteria like E. coli, Staphylococcus aureus and Candida albicans and also checked microbial protein expression.…”
Section: Acv Act As Antioxidants Antimicrobial and Antifungalmentioning
confidence: 99%
“…Apples are consumed raw, and also in the form of apple sauce, juice, concentrates, wine, vinegar, or slices, depending on their seasonality, low durability, and low disease resistance. In particular, apple vinegar and wine not only reduce cholesterol levels and improve antioxidant capacity, but also help regulate metabolism (Seydim, Guzel-Seydim, Doguc, Savas, & Budak, 2016). Complex physical, chemical, and biological changes are involved during different kinds of apple processing.…”
Section: Introductionmentioning
confidence: 99%